Evolution of Climatic Related Leaf Traits in the Family Nothofagaceae - Glade-Vargas, Nataly; Hinojosa, Luis F.; Leppe, Marcelo (Frontiers in Plant Science, 2018)
The current relationship between leaf traits and environmental variables has been widely used as a proxy for climate estimates. However, it has been observed that the phylogenetic relationships between taxa also influence the evolution of climatic related leaf traits, implying that the direct use of the physiognomy-climate relation should be corrected by their ancestor-descendant relations. Here we analyze the variation of 20 leaf traits during the evolution of 27 species in the Gondwana family Nothofagaceae. We evaluate whether the evolution of these traits is exclusively associated with past climate variations or whether they are restricted by phylogenetic relationships. Our results indicate that four leaf traits, associated with size and shape, had consistently a phylogenetic independent evolution, suggesting adaptive variation with the environment. While three of the traits, presented consistently phylogenetic signal and fit a Brownian motion or Ornstein-Uhlenbeck model of evolution, suggesting that the evolution of these traits is restrained by phylogenetic relationships and implying that phylogenetic corrections should be made for the family Nothofagaceae to use them as climatic proxy. Finally, this study highlights the importance of evaluating the evolutionary history of climatic related leaf traits before conducting paleoclimate estimates.